The −251 A/T Polymorphism in the IL8 Promoter is a Risk Factor for Acute Pancreatitis. Issue 1 (January 2018) - Bishu, Shrinivas; Koutroumpakis, Efstratios; Mounzer, Rawad; Stello, Kimberly; Pollock, Nijole; Evans, Anna; Whitcomb, David C.; Papachristou, Georgios I.
Abstract : Objectives: Inflammation in the setting of acute pancreatitis (AP) is partially driven by pathogen recognition receptors that recognize damage-associated molecular patterns. Interleukin (IL)-8 is a chemotactic factor produced by pathogen recognition receptor-expressing cells. A single-nucleotide polymorphism in IL8 promoter region (−251 A/T) has been implicated in inflammatory diseases. We examined whether this IL8 polymorphism confers susceptibility to AP. Methods: Patients with AP (n = 357) were prospectively recruited. Clinical data and blood were collected in subjects and controls (n = 347). Severity was defined following the Revised Atlanta Classification. Genotypes were assessed by quantitative polymerase chain reaction using TaqMan probes. Results: Patients and controls had similar demographics and had no difference in Hardy-Weinberg (patients, P = 0.29; controls, P = 0.66). Twenty-five percent of patients developed severe AP. Compared with controls, the A/A genotype was more common in AP ( P = 0.041; odds ratio, 1.42; 95% confidence interval, 1–1.99). Obese patients with the A/A genotype were more likely to develop mild AP ( P = 0.047). Conclusions: The −251 polymorphism confers susceptibility to AP and disease severity in obese patients. However, its effect is moderate. One potential mechanism for this susceptibility is via increased IL8 production by innate cells, with subsequent enhanced neutrophil influx and pancreatic injury.